PCR enzyme-linked immunosorbent assay for diagnosis of leishmaniasis in human immunodeficiency virus-infected patients. - Costa, J M (1996)
A PCR enzyme-linked immunosorbent assay (ELISA) involving the use of bone marrow aspirates (BMA) and blood samples (BS) for the diagnosis of visceral leishmaniasis (VL) in human immunodeficiency virus-infected patients was developed with primers selected from the sequence of the small-subunit rRNA gene and compared with direct examination and in vitro cultivation. The PCR was optimized for routine diagnosis: processing of samples with lysis of erythrocytes without isolation of leukocytes, enzymatic prevention of contamination, internal control of the reaction, and ELISA testing in a microtitration plate hybridization. Of 79 samples (33 BMA and 46 BS) from 77 patients without VL, all the results were negative. Fifty-three samples (9 BMA and 44 BS) were obtained from 13 patients with VL: 6 samples drawn during anti-Leishmania treatment were negative whatever the technique used, and 47 samples (9 BMA and 38 BS) were positive with at least one technique. The sensitivities were 51% (24 of 47), 81% (38 of 47), and 98% (46 of 47) for direct examination, culture, and PCR, respectively. Thus, PCR ELISA is reliable for diagnosing VL in human immunodeficiency virus-infected patients, and blood sampling should be sufficient for the follow-up.